The search engine that was something more - Millán, José-Antonio (Anuario ThinkEPI, 2011)
The changes that Google have introduced in the search results for "guessing" user´s preferences, and trying to give results closer to their intended search targets (and also for the sake of advertising), can hinder some uses of the search engine. For example, unlike when it was less "intelligent", now Google gives biased results toward local information deemed to be nearer to the user, or corrects the spelling of common terms when looking for the unusual ones.
Keywords: Search engines; User knowledge; Results ranking; Bias; Intelligent search.